Influenza A Virus Inhibits RSV Infection via a Two-Wave Expression of IFIT Proteins - Drori, Yaron (Viruses, 2020)
Influenza viruses and respiratory syncytial virus (RSV) are respiratory viruses that primarily circulate worldwide during the autumn and winter seasons. Seasonal surveillance has shown that RSV infection generally precedes influenza. However, in the last four winter seasons (2016–2020) an overlap of the morbidity peaks of both viruses was observed in Israel, and was paralleled by significantly lower RSV infection rates. To investigate whether the influenza A virus inhibits RSV, human cervical carcinoma (HEp2) cells or mice were co-infected with influenza A and RSV. Influenza A inhibited RSV growth, both in vitro and in vivo. Mass spectrometry analysis of mouse lungs infected with influenza A identified a two-wave pattern of protein expression upregulation, which included members of the interferon-induced protein with the tetratricopeptide (IFITs) family. Interestingly, in the second wave, influenza A viruses were no longer detectable in mouse lungs. In addition, knockdown and overexpression of IFITs in HEp2 cells affected RSV multiplicity. In conclusion, influenza A infection inhibits RSV infectivity via upregulation of IFIT proteins in a two-wave modality. Understanding the immune system involvement in the interaction between influenza A and RSV viruses will contribute to the development of future treatment strategies against these viruses.